2013
DOI: 10.2147/ppa.s40173
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to monthly online self-assessments for short-term monitoring: a 1-year study in relapsing-remitting multiple sclerosis patients after start of disease modifying treatment

Abstract: BackgroundThe participation of neurologists and patients in studies on the effectiveness and safety of newly authorized drugs in multiple sclerosis (MS) is insufficient. Monthly online self-assessments using patient-reported outcomes may help in short-term monitoring of neurological changes and side effects.ObjectiveInvestigate in relapsing-remitting (RR) MS patients the adherence to monthly online self-assessments after the start of disease modifying treatment.MethodsObservational study in 39 neurological dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…Moreover, in the glatiramer acetate study, patients were included by their treating neurologists at the time of treatment initiation, whereas in this study, patients enrolled themselves at an arbitrary point in time. Nonetheless, the median monthly interassessment intervals (30-32 days) and the median baseline-M24 interval ([2x365]+19 days) in this study compare favorably with the median interassessment intervals (32-34 days) and the median baseline-M12 interval (365+52 days) in our previous study [ 12 ].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Moreover, in the glatiramer acetate study, patients were included by their treating neurologists at the time of treatment initiation, whereas in this study, patients enrolled themselves at an arbitrary point in time. Nonetheless, the median monthly interassessment intervals (30-32 days) and the median baseline-M24 interval ([2x365]+19 days) in this study compare favorably with the median interassessment intervals (32-34 days) and the median baseline-M12 interval (365+52 days) in our previous study [ 12 ].…”
Section: Discussionsupporting
confidence: 75%
“…In this study, 64.0% of the patients had completed all monthly MA questionnaires 1 year after baseline. In a previous 1-year study in MS patients who started daily glatiramer acetate treatment, we found that 75.5% of the patients completed all monthly short questionnaires on fatigue (five items) and HRQoL (eight items) [ 12 ]. This higher percentage could relate to the content of the questionnaires: fatigue is a frequent and often debilitating symptom in MS that was expected to improve during glatiramer acetate treatment, whereas the documentation of medication and missed DMD doses may be less appealing to patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More frequent assessments and the use of patient-reported outcomes (PROs) could have an added value. 6 , 7 …”
Section: Introductionmentioning
confidence: 99%